An Analysis of Eminent Persons’ Group (EPG) Meetings and its Significance - Bogati, Prithivi Bahadur (Research Journal on Multi-disciplinary Issues, 2021)
This paper explores the feedback and long-term solution by wiping out the disputes and long misunderstandings regarding bilateral relations between Nepal and India. Two years’ tenure has completed of this Eminent Persons’ Group (EPG) in July, 2018, where nine meetings are held on both sides Nepal and India in a rotation basis. There were four members from each Eminent Persons’ Group, and in total eight members from the various intellectual fields were involved. This paper highlights on the overall EPG meetings; trade and transportation, information technology, development, water resources, border security and mostly Treaty of Peace and Friendship along with other various issues. This paper claims that this report is not the mandatory for the both governments; it is just a suggestion. The experts’ views and more profound study and analysis of both groups may give guidelines for the both governments to carry on the sound bilateral relationship. The joint report will develop the cultural, social, political relation positively between the two countries erasing the misunderstanding and correcting the unequal bilateral treaties/ relations. For the implementation of this report on the ground, the goodwill of both governments is necessary.